Preparation and characterization of [68Ga]NODAGA-Pamidronic acid for pet bone cancer imaging - Mohd Ashhar, Zarif Naim (2020)
Early detection of bone metastases is essential to prevent skeletal-related events. Unlike biopsies, a non-invasive technique to diagnose bone metastases is by utilizing radiopharmaceuticals and detected using a nuclear imaging modality. Hence, this research deems to determine the role of gallium-68 radiolabeled bisphosphonates ([68Ga]NODAGA-Pamidronic acid) for PET bone cancer imaging. This study aims to ascertain the preparation, characterization, and radiolabeling of [68Ga]NODAGA-Pamidronic acid. Lastly, to determine its potential application, the in vitro bone binding assay and in vivo bone-to-blood ratio is examined. Firstly, NODAGA-Pamidronic acid (NODPAM) was prepared via the NHS ester conjugation method and characterized using tandem mass spectrometry (MS/MS). The RP-HPLC method was then developed to remove the free NODAGA using 0.1% trifluoroacetic acid and water as the mobile phase at a flow rate of 0.5 ml/ min. Based on the MS/MS analysis of NODPAM, the precursor ion and product ion observed were according to the theoretical value (theoretical [M-H]-m/z: 591.14, obtained [M-H]-m/z: 591.14, [M-H-H3PO3]-m/z: 509.17). The isotopic abundance M+1 (calculated m/z: 22.02, obtained m/z: 20.99±0.94) confirms the molecular formula C18H34N4O14P2. The HPLC method developed shows a good separation between peaks with a resolution of 1.613. The freeze-dried NODPAM produces a solid white powder. Next, the radiolabeling of [68Ga]NODPAM was optimized by looking into three parameters; pH, temperature, and amount NODPAM. Finally, the in vitro bone binding assay and in vivo bone-to-blood ratio was determined using synthetic hydroxyapatite and Sprague Dawley rats, respectively. From the results obtained, the %RCP of radiolabeled [68Ga]NODPAM was above 90% within 15 minutes at pH 4-4.5 and a temperature of above 60ºC. The in vitro hydroxyapatite (HA) bone binding assay displayed a significant difference between the [68Ga]NODPAM 82.25%±1.72 and [99mTc]MDP of 53.21%±0.28 (p<0.05). The bone-to-blood ratio of [68Ga]NODPAM 2-hour post-injection was significantly higher (P<0.05) compared to 68Ga(III); 27.53 and 0.74, respectively. In conclusion, [68Ga]NODPAM was prepared and characterized accordingly, and the in vitro bone binding assay and in vivo bone-to-blood ratio were assessed. The preliminary data suggests that there is a need for a complete pre-clinical study of [68Ga]NODPAM before translating it into clinical research.